Frequency of vascular risk factors and the impact of their treatment on the outcome of acute ischemic stroke in patients treated with recanalization therapy - Mikulan, Rea; Macura, Lana; Pađen, Višnja (Medicinski podmladak, 2024)
ABSTRACT:Introduction: Stoke is one of the leading causes of death and longterm disability worldwide. Timely diagnosis and control of vascular risk factors is a priority for stroke prevention.Material and methods :A retrospective analysis of data on stroke patients treated with recanalization therapy in a one-year period was performed. The analysis contained the characteristics of the study population, risk factors and comorbidities and the therapy used in stroke primary prevention. Symptomatic intracerebral haemorrhage (sICH) was defined according to ECASS-2 criteria. Patients' functional outcome after three months was assessed by using a modified Rankin scale score (mRS).Results: The study included a total of 117 stroke patients of whom 70 (60%) were small. The average age of the study population was 65 years (64.6 ± 14), with a baseline NIHSS score of 12 (12 ± 6.7). The most often present risk factors were arterial hypertension and hypercholesterolemia. The most commonly used drugs in primary prevention were antihypertensives and antithrombotic therapy. Afterwards, patients were divided into two groups (those with previous antithrombotic (AT) therapy and those without). Patients who were not on previous AT therapy were: more often male, aged 45-75 years or younger than 45 years, less often had previous AF, hypercholesterolemia and previous stroke. They also had a trend of initially lower NIHSS score. There were no statistical differences in the occurence of sICH between the two groups.Conclusion: The identification of stroke risk factors within all age groups and their treatment is of great importance in primary prevention of stroke. A previous use of antithrombotic therapy does not increase the likelihood of sICH occurence in stroke patients treated with recanalization therapy.
Keywords: acute ischemic stroke, primary prevention, recanalization therapy, outcome